Case Report: Rehabilitation and Return to Running Program for Shin Splints Runners. - Dipta Hiqmal Wirananta; Farid Rahman (Universitas Pendidikan Indonesia, 2024)
Shin splints, also known as medial tibial stress syndrome, is an overuse injury often caused by running. This injury occurs more often in women than men and is the third most common injury in runners. Research on rehabilitation and training plans to return to running after shin splint injuries, especially to return to exercise phase, has not been extensively researched. The aim of this article was to study the training to return to running and physiotherapy management in rehabilitation programs for amateur runners experiencing shin splints in the return to exercise phase. A male amateur runner who met the requirements, including had completed a long distance run (at least 21 km) and experienced shin splints in the return to exercise phase, was the subject of this case report study. The patient did not have any new complaints or specific complications, especially after starting an exercise program. On the contrary, the patient progress improved over time. Based on research findings, an amateur runner with complaints of shin splints in the superolateral third of the tibia, in the return to exercise phase, gained a benefit from the therapeutic intervention in the form of an exercise and rehabilitation program based on the FITT concept. The program includes a variety of training components, including strengthening, plyometrics, and running, and can also improve performance.